Understanding The Relationship between HRM Practices and Organization Performance in HDFC Bank - ZAR, RAFIA GUL (Archives of Business Research, 2017)
The main purpose of this paper is to understand the relationship between HRM Practices and organizational performance and to evaluate the perceptions of managers and non- managers on HRM practices in the context of HDFC Bank. The data was randomly collected from 24 managers and 72 subordinates using a self-administered questionnaire. The research study empirically evaluated the nine HRM practices (General climate, OCTAPACE Culture, Selection Process, Job Definition, Career Planning, Employee Participation, Performance Appraisal, Training and Development and compensation). The study showed that there is direct relationship between HRM practices and organizational performance. Finally, this research study depicts the limitations, suggestions and future research directions.